Taxonomic review of the genus Parastacus Huxley, 1879 (Decapoda: Astacidea: Parastacidae) with description of five new species - Ribeiro, Felipe Bezerra; Araujo, Paula Beatriz (Zootaxa, 2024)
The freshwater crayfish genus Parastacus Huxley, 1879 (Parastacidae) is reviewed. Seven species are redescribed: Parastacus brasiliensis (von Martens, 1869), P. defossus Faxon, 1898, P. laevigatus Buckup & Rossi, 1980, P. pilimanus (von Martens, 1869), P. pugnax (Poepigg, 1835), P. promatensis Fontoura & Conter, 2008, and P. varicosus Faxon, 1898. In addition, five new species are described: Parastacus bah, P. heterochaelis, P. manezinho, P. quasimodo and P. rudolphi. Descriptions, diagnoses, and synonyms of the genus and species are provided. In addition, information on the geographical distribution and an identification key is presented for all species.